Improving Student Engagement in Indonesian Language Learning Through Literacy-Based Learning in Elementary School - Nasy-ah Nur Firdousi; Natiaz Malita Barqi; Malika Putri Sefia; Levina Galuh; Zakia Anil Hawa; Tyasmiarni (Yayasan Citra Dharma Cindekia, 2026)
This study aims to improve elementary students’ Indonesian literacy learning engagement through the implementation of literacy-based learning. The study focuses on enhancing student engagement across key literacy-based activities, including reading, questioning, answering, discussing, and completing learning tasks. This research employed classroom action research (CAR), conducted in two cycles, each consisting of planning, acting, observing, and reflecting stages. The participants were 28 fifth-grade student. Data were collected through observation and documentation using a student engagement observation sheet. The data were analyzed using descriptive quantitative methods by calculating the percentage of student engagement in each cycle. The findings revealed a significant improvement in student engagement within the literacy learning process. In Cycle I, only 50% of students were categorized as active , whereas in Cycle II, 100% of students reached the active and very active categories. These results indicate that literacy-based learning is effective in improving students’ learning engagement and participation during Indonesian literacy lessons. It also creates a more interactive and meaningful learning environment.